Kinetics and mechanism of permanganate oxidation of nalidixic acid in aqueous alkaline medium - Ankita Jain, Gajala Tazwar, Vijay Devra (Journal of Applied Pharmaceutical Science, 2017)
The kinetics and mechanism of oxidation of nalidixic acid (NA) by permanganate ion in alkaline medium have been studied at 40 ± 1oC. The Stoichiometry was observed to be 2:1 in terms of mole ratio of permanganate ion and nalidixic acid consumed. The reaction shows first order with respect to oxidant and fractional order in both the substrate and alkali concentration. The oxidation reaction proceeds via an alkali permanganate species that forms a complex with nalidixic acid and the complex then decomposes to give the product. The effects of added products and ionic strength have also been investigated. The main products identified were hydroxylated NA and Mn(VI). A mechanism was proposed on the basis of experimental results. Investigation of the reaction at different temperature allowed the determination of the activation parameters with respect to the slow step of the proposed mechanism.
Keywords: Kinetics, oxidation, mechanism, nalidixic acid, permanganate ion.